Multidisciplinary Management of Maxillary Regional Odontodysplasia. (2nd January 2019) - Jeffery, Shahrzad; Brock, Gareth R; Harrison, Jayne E; Butterworth, Chris J
Abstract : This case report describes the multidisciplinary clinical management of a male patient, diagnosed at the age of 7, with Regional Odontodysplasia of the right maxilla. Following fixed orthodontic treatment to align his teeth, extraction of malformed teeth and subsequent bone grafting, the patient was successfully rehabilitated with implant-supported bridgework of a hybrid design to replace the teeth in the right maxillary quadrant. Clinical steps, as well as the complexities of this particular case, will be described. CPD/Clinical Relevance: This case highlights the need for a multidisciplinary team approach to provide comprehensive care for patients with complex dental anomalies.